Notch signaling in cancer: metabolic reprogramming and therapeutic implications - Wang, Shuang-Shuang; Lv, Hui-Lin; Nie, Rong-Zu; Liu, Ya-Ping; Hou, Yan-Jie; Chen, Chen; Tao, Xing-Yue; Luo, Huo-Min; Li, Pei-Feng (Frontiers in Immunology, 2025)
The evolutionarily conserved Notch signaling pathway is essential for cell-fate determination, organogenesis, and tissue homeostasis. Notch receptors and their ligands are transmembrane proteins with epidermal growth factor–like repeats; ligand–receptor binding triggers canonical Notch signaling. Notch signaling is context dependent in cancer, functioning as either an oncogene or a tumor suppressor. Aberrant Notch activation promotes epithelial–mesenchymal transition, sustains cancer stem–like phenotypes, and drives metabolic reprogramming, thereby facilitating tumor progression and therapeutic resistance. Current clinical efforts target the pathway with γ-secretase inhibitors (GSIs), monoclonal and bispecific antibodies, and synthetic Notch (synNotch) approaches. Clinical translation, however, is constrained by dose-limiting toxicity, a paucity of predictive biomarkers, and compensatory resistance through intersecting pathways. Priorities for future work include the development of highly selective Notch modulators, biomarker-guided combination regimens, and targeted delivery systems to realize the translational potential of Notch-targeted therapies in precision oncology.